“Diseño y simulación de un timón de dirección eléctrico adaptable con las sillas de ruedas para mejorar la movilidad de las personas discapacitadas”. - Mejía Herrera, Diego Xavier (2020)
Designing and simulation of an adaptable electric rudder with wheelchairs is reflected in this research since in the country there is no research related to this issue, this technological proposal was born when saw the disabled people’s need, in order to propose an alternative that in the future can be implemented and serve this for them. those people who suffer from physical disabilities in their legs deserve to be taken into account and through it hope is being given since in the near future this research may serve as the basis for the electric rudders adaptable with wheelchairs conventional manufacture and thus improve the lifestyle. the designing and simulations carried out in software allow to have a clear idea of the operation and reliability of both the materials and the mechanism subjected to regular loads between 51kg - 74kg. a pedal rudder was taken as a reference to design it, , measurements were made and the different mechanisms that make up the rudder were drawn, adapting the drive system, battery and charging system, braking system, and steering system; data were compared between calculations of the position angles and the measurements provided by the software, the corresponding simulations were carried out following their respective regulations and for the application, several factors that influence it were taken into account, such as ergonomics, average weight of an adult person, the height of the rudder handlebar among others, finally the simulation of the technological proposal was concluded, verifying its operation by means of the finite element method.